2020
DOI: 10.1371/journal.pone.0242457
|View full text |Cite
|
Sign up to set email alerts
|

The complex geographies of telelactation and access to community breastfeeding support in the state of Ohio

Abstract: The availability of breastfeeding support resources, including those provided by Baby-Friendly Hospitals, International Board Certified Lactation Consultants, breastfeeding counselors and educators, and volunteer-based mother-to-mother support organizations, such as La Leche League, are critically important for influencing breastfeeding initiation and continuation for the mother-child dyad. In addition, the emergence of community support options via information and communication technologies such as Skype and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…There are large inequalities in infant feeding experience along structural lines in the UK and similar HIC (Victora et al, 2016), contributing to socioeconomic gradients in inflammation and infant weight (McDade & Koning, 2021). These inequalities exist due to cultural and religious norms around breastfeeding, particularly in public (Chang et al, 2021), access to social support (Grubesic & Durbin, 2020;Tomori, 2009), opportunity costs of breastfeeding (Hough et al, 2018;Tully & Ball, 2018), as well having convenient and quickto-access places to breastfeed (Brown et al, 2020;Hauck et al, 2020). Furthermore, the experience of breastfeeding problems is unlikely to be evenly distributed as one study found that young, unmarried and non-college educated US women were more likely to experience breastfeeding problems resulting in disrupted lactation (Stuebe et al, 2014).…”
Section: Hypothesis 3: the Type Of Support Impacts The Moderating Effectmentioning
confidence: 99%
“…There are large inequalities in infant feeding experience along structural lines in the UK and similar HIC (Victora et al, 2016), contributing to socioeconomic gradients in inflammation and infant weight (McDade & Koning, 2021). These inequalities exist due to cultural and religious norms around breastfeeding, particularly in public (Chang et al, 2021), access to social support (Grubesic & Durbin, 2020;Tomori, 2009), opportunity costs of breastfeeding (Hough et al, 2018;Tully & Ball, 2018), as well having convenient and quickto-access places to breastfeed (Brown et al, 2020;Hauck et al, 2020). Furthermore, the experience of breastfeeding problems is unlikely to be evenly distributed as one study found that young, unmarried and non-college educated US women were more likely to experience breastfeeding problems resulting in disrupted lactation (Stuebe et al, 2014).…”
Section: Hypothesis 3: the Type Of Support Impacts The Moderating Effectmentioning
confidence: 99%
“…These locations are potentially ripe for education programs, additional Baby-Friendly hospitals, or community-based efforts to enhance local breastfeeding support structures. These efforts might include International Board Certified Lactation Consultants (IBCLCs), La Leche League, Breastfeeding USA, Baby Café, or telelactation programs if quality (and affordable) internet services are available [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Social and environmental issues included economic difficulties in obtaining access to SNSs and vulnerable communication environments ( e.g., Wi-Fi service). 25 , 30 , 36 , 44 These social and environmental issues are faced by many mothers all over the world. To overcome this, social support is needed to bridge the digital divide.…”
Section: Discussionmentioning
confidence: 99%